Combined Physiology and Transcriptome Analyses Provide Insights into Malformed Fruit of Cocos nucifera L. - Lilan Lu; Zhiguo Dong; Yuan Zhang; Siting Chen; Qingxin Wu (Agriculture)
Malformed coconut fruit occurrence exhibits dual impacts on agricultural productivity and economic returns, primarily through substantial yield reduction and compromised commercial value resulting from morphological defects. To elucidate the molecular determinants underlying this developmental anomaly, we conducted a systematic investigation integrating physiological profiling and transcriptomic sequencing on pulp tissues from malformed (MF) and normal (NF) coconut fruits. Notably, MF specimens displayed marked depletion in carbohydrate reserves, with soluble sugars (SS), reducing sugars (RS), starch (SH), soluble proteins (SP), and fat (FA) declining by 28.57%, 20.43%, 15.51%, 36.78%, and 50.18%, respectively, compared to NF controls. Conversely, a coordinated upregulation of phytohormones was observed, where indole acetic acid (IAA), abscisic acid (ABA), cytokinin (CK), gibberellic acid (GA), brassinosteroid (BR), jasmonic acid (JA), and salicylic acid (SA) levels increased by 31.82–92.97%, while ethylene (ETH) exhibited a paradoxical 30.09% reduction. Transcriptomic dissection revealed 6370 functionally annotated differentially expressed genes (DEGs), comprising 4235 upregulated and 2135 downregulated transcripts. These DEGs were predominantly enriched in critical pathways including plant hormone signal transduction, flavonoid/phenylpropanoid biosynthesis, and carbohydrate metabolic networks. Particularly noteworthy was the enhanced activity of cell wall remodeling enzymes—cellulase (CEL), polygalacturonase (PG), and pectinesterase (PE)—accompanied by differential expression of nine cell wall-associated gene families (CEL, PE, PG, PEL, URG, UTR, VTC2, EXP, XET/XTH) and eight phytohormone-related gene clusters. Functional stratification analysis further identified key transcriptional regulators, with MYB, ERF/AP2, BHLH, WRKY, bZIP, and MADS transcription factors demonstrating significant expression divergence, suggesting their pivotal regulatory roles in MF pathogenesis. This multi-omics integration not only deciphers the molecular choreography of coconut fruit malformation but also establishes a novel conceptual framework for developmental disorder research in perennial crops.